Regulation of chemokine expression in human airway smooth muscle cells - Binnion, Amy Margaret (2010)
Asthma is an inflammatory disease of the airways characterised by airway remodelling and hyperresponsiveness. New treatments are needed for patients with severe asthma whose disease is not controlled with currently available therapies. Asthma pathophysiology is complex, however, accumulating evidence suggests multiple inflammatory pathways in asthma converge onto a relatively small number of downstream targets that may be of therapeutic interest. These include mitogen activated protein kinases (MAPKs), the pro-inflammatory transcription factors nuclear factor-kappaB (NF-kappaB) and activator protein-1 (AP-1) and transcriptional regulators such as histone acetyl transferases (HATs) and histone deacetylases (HDACs). Chemokines are molecules secreted at sties of inflammation, attracting inflammatory cells and perpetuating the inflammatory response. Here we studied the mechanisms by which the pro-inflammatory mediator endothelin-1 (ET-1) and the cytokine tumour necrosis factor-alpha (TNF-alpha) promoted expression by primary human airway smooth muscle cells (HASMC) of two important chemokines, monocyte chemotactic protein-1 (MCP-1) and eotaxin. Further, we studied the mechanisms by which existing asthma therapies (long acting beta agonists (LABA) and glucocorticoids) modulated TNF-alpha-stimulated eotaxin expression. Endothelin-1 stimulated MCP-1 release through a transcriptional mechanism involving NF-kappaB and AP-1; the upstream signalling pathway involved p38 and p44/p42 MAPKs. Previously, this lab showed that TNF-alpha-induced eotaxin release is also NF-kappaB-dependent, involving histone H4 acetylation at the eotaxin promoter. Here we found that TNF-alpha-induced eotaxin release does not involve histone H3 acetylation, and that TNF-alpha-dependent histone H4 acetylation does not occur through alterations in total histone activity or levels of the key HDACs -1 and -2. Similarly, modulation of TNF-alpha effects on eotaxin expression by glucocorticoids and LABA is independent of total HDAC activity and HDAC-1 and -2 levels. These studies support the body of evidence suggesting that multiple inflammatory pathways in asthma converge onto a small number of downstream targets, and are relevant to the understanding and treatment of asthma.